Tlc Profile And Antifungal Activity Test Of Ethylacetat Extract Of The Flower Moon Herbs (Tithoniadiversifolia (Hemsl.) Gray) Againts Candida Albicans And Microsporum Canis - Hepni Hepni; Fitri Yanti; Faisal Yusuf (Journal of Midwifery and Nursing, 2022)
The moon flower herb is a plant species known and used as traditional medicine in Indonesia for generations. In previous studies it was known that moonflower (Tithonia diversifolia (Hemsl) Gray) has antihyperglycemic, antidiabetic, antimicrobial and antimalarial effects, and it is known that the roots, stems, leaves and essential oil of moonflower (Tithonia diversifolia (Hemsl) Gray) contain alkaloids, compounds phenolics, steroids, saponins and flavonoids. The purpose of this study was to determine the activity of ethylacetate extract of moonflower herb against Candida albicans and Microsporum canis. This research was carried out in several stages, starting with the process of collecting and processing samples, testing the characteristics of simplicia, maceration of the ethylacetate extract of the moonflower herb (Tithonia diversifolia (Hemsl) Grey), testing Thin Layer Chromatography (TLC) and testing antifungal activity. The results of the research that the moon flower herb has a water content of about 10.2%. Thin Layer Chromatography (TLC) test of moonflower herbs on ethyl acetate extract containing polyphenolic compounds, steroids and alkaloids. The minimum inhibitory concentration (MIC) of ethylacetate extract of moonflower herb against Candida albicans ATCC 10231 was at a concentration of 200 mg/mL, ie 3.00 mm, while in Microsporum canis it was found at a concentration of 300 mg/mL. which is equal to 13.21mm.